Activation of TRPM7 by naltriben enhances migration and invasion of glioblastoma cells - Wong, Raymond (Oncotarget, 2017)
Glioblastoma (GBM), the most common and aggressive brain tumor in the central nervous system, remains a lethal diagnosis with a median survival of < 15 months. Aberrant expression of the TRPM7 channel has been linked to GBM functions. In this study, using the human GBM cell line U87, we evaluated the TRPM7 activator naltriben on GBM viability, migration, and invasiveness. First, using the whole-cell patch-clamp technique, we showed that naltriben enhanced the endogenous TRPM7-like current in U87 cells. In addition, with Fura-2 Ca(2+) imaging, we observed robust Ca(2+) influx following naltriben application. Naltriben significantly enhanced U87 cell migration and invasion (assessed with scratch wound assays, Matrigel invasion experiments, and MMP-2 protein expression), but not viability and proliferation (evaluated with MTT assays). Using Western immunoblots, we also detected the protein levels of p-Akt/t-Akt, and p-ERK1|2/t-ERK1|2. We found that naltriben enhanced the MAPK/ERK signaling pathway, but not the PI3k/Akt pathway. Therefore, potentiated TRPM7 activity contributes to the devastating migratory and invasive characteristics of GBM.